2022
DOI: 10.3389/fgene.2022.866169
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Penetrance of Population-Based Genetic Screening Results in Electronic Health Record

Abstract: The clinical value of population-based genetic screening projects depends on the actions taken on the findings. The Healthy Nevada Project (HNP) is an all-comer genetic screening and research project based in northern Nevada. HNP participants with CDC Tier 1 findings of hereditary breast and ovarian cancer syndrome (HBOC), Lynch syndrome (LS), or familial hypercholesterolemia (FH) are notified and provided with genetic counseling. However, the HNP subsequently takes a “hands-off” approach: it is the responsibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 43 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…In the general population, there is less evidence on the uptake of preventive strategies or outcomes. Several studies indicate that many BRCA1 /2 carriers identified through population screening do undergo risk-reducing procedures such as surveillance or prophylactic surgery ( Buchanan et al, 2020 ; Lee et al, 2021b ; Elhanan et al, 2022 ). In some cases, HBOC-associated cancers were diagnosed because of the screening initiated based on the genomic screening results ( Buchanan et al, 2020 ).…”
Section: Are There Accepted Options For Surveillance and Prevention F...mentioning
confidence: 99%
See 4 more Smart Citations
“…In the general population, there is less evidence on the uptake of preventive strategies or outcomes. Several studies indicate that many BRCA1 /2 carriers identified through population screening do undergo risk-reducing procedures such as surveillance or prophylactic surgery ( Buchanan et al, 2020 ; Lee et al, 2021b ; Elhanan et al, 2022 ). In some cases, HBOC-associated cancers were diagnosed because of the screening initiated based on the genomic screening results ( Buchanan et al, 2020 ).…”
Section: Are There Accepted Options For Surveillance and Prevention F...mentioning
confidence: 99%
“…Evidence on the outcomes of population genomic screening for LS beyond detection rate is limited. Several studies of population genomic screening for LS have found that a proportion of individuals with pathogenic LS variants underwent risk-reducing procedures, including colonoscopy and prophylactic surgery ( Buchanan et al, 2020 ; Lee et al, 2021b ; Elhanan et al, 2022 ). Several individuals were diagnosed with LS-associated cancers because of follow-up initiated based on their genomic screening results ( Buchanan et al, 2020 ).…”
Section: Are There Accepted Options For Surveillance and Prevention F...mentioning
confidence: 99%
See 3 more Smart Citations